The Effect of Economic Value Added (EVA) and Market Value Added (MVA) on Stock Returns - Khairun Nisa; Budi Santoso; Burhanudin Burhanudin (Jurnal Syntax Transformation, 2024)
This study analyze the factors that affect stock returns in food and beverages companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The variables in this study are Economic Value Added (EVA) and Market Value Added (MVA). This research was conducted using multiple linear regression analysis. The data collection tools used are literature study and documentation with purposive sampling method. The sample used in this study were 12 companies from a total population of 30 companies. The results of this study indicate that the higher or lower the value of Economic Value Added (EVA) does not affect the value of Stock Return, as well as the higher or lower value of the Market Value Added (MVA) also does not affect the Stock Return.